Civil society, international courts and compliance bodies : a project of the Universities of Milano, Brescia and Verona with the co-operation of PICT-The Project of International Courts..., por Tullio Treves, y otros, La Haya : Chiara Ragni Editores, 2005 - González Bodor, Fernando (Estudios Internacionales, 2005)
-